Transition-Metal-Catalyzed Alkyl Heck-Type Reactions - Kurandina, Daria; Chuentragool, Padon; Gevorgyan, Vladimir (Synthesis, 2019)
The Heck reaction is one of the most reliable and useful strategies for the construction of C–C bonds in organic synthesis. However, in contrast to the well-established aryl Heck reaction, the analogous reaction employing alkyl electrophiles is much less developed. Significant progress in this area was recently achieved by merging radical-mediated and transition-metal-catalyzed approaches. This review summarizes the advances in alkyl Heck-type reactions from its discovery early in the 1970s up until the end of 2018.1 Introduction2 Pd-Catalyzed Heck-Type Reactions2.1 Benzylic Electrophiles2.2 α-Carbonyl Alkyl Halides2.3 Fluoroalkyl Halides2.4 α-Functionalized Alkyl Halides2.5 Unactivated Alkyl Electrophiles3 Ni-Catalyzed Heck-Type Reactions3.1 Benzylic Electrophiles3.2 α-Carbonyl Alkyl Halides3.3 Unactivated Alkyl Halides4 Co-Catalyzed Heck-Type Reactions5 Cu-Catalyzed Heck-Type Reactions6 Other Metals in Heck-Type Reactions7 Conclusion
Keywords: Heck reaction; cross-coupling; alkyl halides; alkenes; transition-metal catalysis